STRATEGI PENINGKATAN KINERJA APARATUR PENGELOLA ASET DAERAH DI KABUPATEN TAPANULI TENGAH - Sihombing, Nalom Santun; Rachmina, Dwi; Sarma, Ma’mun (Jurnal Manajemen Pembangunan Daerah, 2016)
A qualified opinion (WDP) on LKPD Tapanuli Tengah Regency has become the focus of attention of the government in revamping asset management. The low performance of local official asset Manager caused problems in fixed assets, namely non-compliance with relevant regulations, operational procedures that are less clearly understood, and administrative error in asset management. The purpose of this sudy were to 1) Describe the system of supervision and controlling of local asset management; 2) Analyze internal and external factors in the asset management dan 3) Formulate strategy for improving the performance of the apparatus asset managers. The method used was the determining factor SWOT IFE and EFE, obtained in the form of a matrix IE grand strategy and prioritized through a matrix of pairwise comparison (pairwise comparisons matrix). This study used 74 respondents from 51 SKPDs composed of heads of office and local official asset managers. The results showed that the highest weight was found in internal factors. For external factors are the central government regulation of governance of regional assets, and governance support in accordance with the rules of government policy in favor of asset management. The highest strategic priority was to increase support government policies, both national and local human resource development to improve the competence of local asset managers through training to facilitate the administration of the assets in accordance with the rules of governance.Key words: External Factor, Good Governance, Internal Factor, Priority strategy, Qualified Opinion  ABSTRAK Opini wajar dengan pengecualian (WDP) atas LKPD Tapanuli Tengah menjadi fokus perhatian pemerintah dalam pembenahan pengelolaan aset. Rendahnya kinerja pengelola aset menyebabkan permasalahan pada aset tetap yaitu ketidakpatuhan terhadap peraturan terkait, prosedur operasional yang kurang jelas dipahami, kesalahan administratif dalam pengelolaan aset. Tujuan penelitian adalah 1) Mendeskripsikan sistem pengawasan dan pengendalian pengelolaan aset daerah, 2) Menganalisis faktor internal dan external pengelolaan aset, 3) Merumuskan strategi peningkatan kinerja aparatur pengelola aset daerah. Metode yang digunakan adalah SWOT (IFE dan EFE), diperoleh grand strategi berupa matriks IE, dan di prioritaskan melalui matriks perbandingan berpasangan (Pairwise comparisons matrix). Sampel penelitian ini terdiri dari 74 responden dari 51 SKPD terdiri dari pejabat dan pengelola aset. Berdasarkan hasil penelitian diperoleh bobot tertinggi pada faktor internal. Untuk faktor eksternal, peraturan pemerintah pusat tentang tata kelola aset daerah, untuk mempermudah tata kelola sesuai dengan aturan kebijakan pemerintah dalam mendukung Pengelolaan Aset. Prioritas strategi tertinggi adalah Meningkatkan dukungan kebijakan pemerintah, baik pusat dan daerah dalam pengembangan SDM dan peningkatan kompetensi pengelola aset daerah melalui pelatihan penatausahaan aset untuk mempermudah tata kelola sesuai dengan aturan.Kata kunci: Faktor Eksternal, Good Governance, Strategi Intensif, Faktor Internal, Strategi Terintegrasi